How the Talmud works - Neusner, Jacob, 1932-2016 (Brill reference library of ancient Judaism, 2002)
The Bavli, or Talmud of Babylonia, the foundation-document of Judaism, its law, theology, and exegesis of Scripture, sets forth an orderly world, resting on reason and tested by rationality. This work covers the problem of the Bavil's intellectual cogency and formal coherence.